Shakespeare, dramatist-philosopher - Pego Puigbó, Armando (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
In this essay a philosophical approach to the dramatic universe of William Shakespeare is proposed beyond the historic, social or aesthetic interpretations which are usual in some current critical theories. Its aim is not primarily to highlight only the philosophical intuitions which are contained in the Shakespere’s work, but to try to show the close philosophical condition of its literary imagination. Though avoiding the excess of the Bardolatry, it is necessary to reexamine the paradoxical relationship which the tragic model of Shakespeare maintains with some categories —and not the rules— of the Aristotelean Poetics. In putting them in check, it may be observed how the theatrical energy of Shakespeare has unveiled some ambiguous territories that the contemporary philosophy is groping as places of the modern invention of «human». Hamlet will be used as example of this capacity to raise a moral and aesthetic debate in interpretations of authors as C. Schmitt, S. Cavell, F. Ricordi o R. Girard.
Keywords: William Shakespeare; poetics; tragedy; literary criticism; contemporary philosophy